Efek Antibiofilm Glass Ionomer Cements dan Resin Modified Glass Ionomer Cements Terhadap Lactobacillus acidophilus - Elsandra Novita Halim; Karlina Samadi; Sri Kunarti (Conservative Dentistry Journal, 2017)
Background: Risk factors for developing secondary caries are similar to those resulting in primary caries. The marginal seal of a restoration is one of the important factors predicting clinical success. The antibiofilm effect of materials used for the luting cement of oral function affects oral health. Antibiofilm properties of dental luting materials such as Glass Ionomer Cement (GIC) and Resin Modified Glass Ionomer Cement (RMGIC) may improve the restorative treatment outcome. Purpose: This experiment evaluates the antibiofilm effect of GIC and RMGIC on Lactobacillus acidophilus in vitro. Method: Lactobacillus acidophilus served as test microorganism. The quantitative microtiter plate biofilm assays were used to evaluate the antibiofilm effect of the dental luting materials on early-stage biofilm using a direct contact test (DCT) then continued by reading of Optical Density (OD) of biofilm using ELISA reader at a wavelength of 570nm. Result: GIC and RMGIC showed a decrease of OD value from negative control in all groups. The materials’ elute had effect on both bacterial growth with GIC higher then RMGIC to inhibit Lactobacillus acidophilus biofilm formation. Conclusion: The antibiofilm effect of GIC more effective than RMGIC to inhibit Lactobacillus acidophilus biofilm formation.